Comparative analysis of strut-and-tie models using Smooth Evolutionary Structural Optimization - Almeida, Valério S.; Simonetti, Hélio Luiz; Oliveira Neto, Luttgardes de [UNESP] (Elsevier, 2013)
The strut-and-tie models are widely used in certain types of structural elements in reinforced concrete and in regions with complexity of the stress state, called regions D, where the distribution of deformations in the cross section is not linear. This paper introduces a numerical technique to determine the strut-and-tie models using a variant of the classical Evolutionary Structural Optimization, which is called Smooth Evolutionary Structural Optimization. The basic idea of this technique is to identify the numerical flow of stresses generated in the structure, setting out in more technical and rational members of strut-and-tie, and to quantify their value for future structural design. This paper presents an index performance based on the evolutionary topology optimization method for automatically generating optimal strut-and-tie models in reinforced concrete structures with stress constraints. In the proposed approach, the element with the lowest Von Mises stress is calculated for element removal, while a performance index is used to monitor the evolutionary optimization process. Thus, a comparative analysis of the strut-and-tie models for beams is proposed with the presentation of examples from the literature that demonstrates the efficiency of this formulation. © 2013 Elsevier Ltd.
Keywords: Evolutionary Structural Optimization; Reinforced concrete structures; Strut-and-tie models; Topology optimization; Comparative analysis; Evolutionary optimizations; Evolutionary structural optimization; Numerical techniques; Performance indices; Structural elements; Strut-and-tie model; Topology Optimization Method; Concrete buildings; Concrete construction; Concretes; Reinforced concrete; Shape optimization; Structural design; Structural optimization; comparative study; concrete structure; deformation mechanism; efficiency measurement; model; optimization; performance assessment; reinforced concrete; stress field